Fatigue Fracture Characteristics of Ti6Al4V Subjected to Ultrasonic Nanocrystal Surface Modification - Xiaojian Cao; Luopeng Xu; Xiaoli Xu; Qingyuan Wang (Metals, 2018)
The influence of ultrasonic nanocrystal surface modification (UNSM) on the fatigue fracture characteristics of Ti6Al4V was investigated. Two groups of specimens were separated due to different heat treatment conditions. Group one was stress-relief annealed at 650 °C, and group two was then treated with solid solution-aging. UNSM with the conditions of a static load of 25 N, vibration amplitude of 30 μm, and 36,000 strikes per unit produced about 40 μm surface severe plastic deformation (SPD) layers on both groups of specimens. UNSM improved the microhardness and the compressive residual stress. UNSM also helped achieve a neat surface, almost without changing the surface roughness. The fatigue strengths of these two groups were improved by 7% and 11.7%, respectively. After UNSM, fatigue cracks mainly initiated from the surface of the specimen before the fatigue life of 106 cycles, while they appeared at the internal compress deformed α-phase at the zone between the SPD layer and the core after the fatigue life of 106 cycles. The cracks usually extended along the deformation overflow bands and the process traces on the surface. Through the change of micro-dimples in the fatigue final rupture region, nanocrystals were achieved in the SPD layer. The crystal slip and the surface remodeling together influenced the energy field of crack evolution.